2002
DOI: 10.1152/ajpendo.00321.2001
|View full text |Cite
|
Sign up to set email alerts
|

Salmon cardiac natriuretic peptide is a volume-regulating hormone

Abstract: The present study tested the hypothesis that salmon cardiac peptide (sCP), a new member of the family of natriuretic peptides, has an important role in the regulation of fluid balance and cardiovascular function. Intra-arterial administration of sCP increased urine output in salmon. It had a diuretic effect in rat as well, but the potency was lower. sCP increased the sodium excretion in proportion to the increased urine flow. Blood pressure was not affected by sCP in either species. Acute volume expansion elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Our previous results have shown that mechanical load is a major stimulus for the secretion of the novel cardiac natriuretic peptide (sCP) (36,42,(65)(66)(67)72). In this study we wanted to characterize the effects of ET-1 on the contractile and endocrine function of the salmon heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous results have shown that mechanical load is a major stimulus for the secretion of the novel cardiac natriuretic peptide (sCP) (36,42,(65)(66)(67)72). In this study we wanted to characterize the effects of ET-1 on the contractile and endocrine function of the salmon heart.…”
Section: Discussionmentioning
confidence: 99%
“…We recently discovered in salmon (Salmo salar) a novel natriuretic peptide hormone, salmon cardiac peptide (sCP), that can serve as a marker of cardiac endocrine function (36,42,(65)(66)(67)72). The physiological effects, structure, and regulation of sCP and its gene resemble those of mammalian natriuretic peptides (65).…”
mentioning
confidence: 99%
“…Eel ANP, CNP and VNP cause natriuresis and diuresis when infused into rats (Takei and Hirose 2002) but, in A. japonica, ANP and VNP cause antidiuresis in seawater-acclimated fish, whereas freshwater-acclimated fish show no change in urine production (Takei and Kaiya 1998;Takei and Balment 1993). Moreover, in salmon, Salmo salar, ANP is diuretic and natriuretic (Tervonen et al 2002). RNase protection assays have located messenger RNA for both NPR-GCs in the kidney of A. japonica (Kashiwagi et al 1999;Katafuchi et al 1994) but their distribution has not been examined.…”
Section: Introductionmentioning
confidence: 99%